Karya Tari Lintas Jiwa dari Spiritualitas Perjuangan dalam Arak Sorban - Humairoo Hasna Zulhanifah; Yan Stevenson; Oktavianus Oktavianus; Wahida Wahyuni (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The dance work LINTAS JIWA is a contemporary abstract dance that explores a social theme and is rooted in the creator’s empirical experiences during the process of higher education. These experiences are shaped by various academic, social, and personal pressures, which are then integrated with the spiritual values of Imam Husein’s struggle as reflected in the Arak Sorban procession of Bengkulu. The values of perseverance, sacrifice, and sincerity serve as the main foundation of this work and are expressed as a reflection of the creator’s inner journey in responding to the dynamics of life. This work is presented as a group dance performed by seven female dancers, symbolizing interconnected and mutually supportive human spiritual journeys. The ideas are not conveyed through a narrative structure, but through symbolic body movements explored intuitively and expressively. The creative process applies Alma M. Hawkins’ method, which consists of exploration, improvisation, composition, and evaluation, resulting in a cohesive and meaningful structure. In addition to movement elements, the work is supported by music and video mapping as visual graphics that enhance the atmosphere and reinforce the meaning of the performance. Through LINTAS JIWA, the creator aims to present a reflective aesthetic experience and to open a space for contemplation on the meaning of struggle in human life.